Assessing vaccine efficacy in influenza clinical trials: challenges and difficulties. Issue 4 (July 2013) - Dewe, Walthere; Benoit, Anne; Legrand, Catherine
The efficacy assessment of an influenza vaccine often requires conducting large and expensive clinical trials. Specificities of influenza increase the complexity of the study designs, of the subsequent statistical analysis and of the interpretation of the results. They include low attack rates, seasonality, multiplicity and frequent mutations of flu viruses as well as heterogeneity of virus circulation, varying annual vaccine composition and so on. The authors discuss how those factors may impact the design, the conduct and the analysis of an efficacy trial and explain why it may fail whatever the true vaccine efficacy. The authors then argue that extending the length to several consecutive seasons is an alternative to the frequently used 1-year design and propose refinements of the statistical models.